PSYCHOLOGICAL DYNAMICS OF REPENTANCE PROCESSESS - AZMI REZA FACHITIANDI; AAD SATRIA PERMADI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Repentance is a form of virtue that must be done by man to ask forgiveness of Allah SWT to escape from sin. In the process of repentance the individual can return to sin. This study aims to describe the psychological dynamics in the process of repentance and repentance factors. This research uses descriptive qualitative approach. Data collection using semi-structured interview techniques. Informants in this study were chosen by purposive sampling which amounted to six people of male gender, having past behavior deviating from social value. From this research, it is found that the problem, seeing the consequences of the behavior of others and comparing oneself with others better can trigger the individual to intention to repent, and being in a deviant environment will make the intention of neglected and return to the sinful deeds, Conformity in repenting make unregulated individuals making it easy to return to sinful acts. There are internal and external support factors in the process of repentance, the internal comes from the individual self that is self-evaluation, self-motivation and self-control, while external factors are stimulus, peer support, intense guidance and social support.